Best Answer

To solve the following equation by substitution, we need to have the equal sign. This will help us group the knowns and the unknowns.

Q: What is Solve By Substitution y0.5x 2 -y-2x 4?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

Algebraic equations with two variables will need two equations to be able to solve it. Then, you can solve it with either substitution, adding/subtracting them together, or graphing! Those are the basic steps... For example: An instance of substitution: 2x + 1 = y + 2 x + y = 3 You could isolate y in the second equation to equal y = 3-x. Then in the first equation, substitute y with what it equals to 2x + 1 = 3-x+2 Then you can solve for x!

(2,3)

The slope of y = 2x - 4 is 2. (y = mx + b, where m is the slope, in this case 2.)

If you mean y = 2x-2 then it is a straight line equation whereas the slope is 2 and the y intercept is -2 and its coordinates would be plotted on the Cartesian plane.

5

Related questions

If you mean: y = x-2 and y = 2x-8 then it works out that x = 6 and y = 4

2

If you mean x+2y = -2 and 3x+4y = 6 then by solving the simultaneous equations by substitution x = 10 and y = -6

You just plug in the value of the given variable. For example: y=3+2 2y=x (now you substitute y for 3+2) 2(3+2)=x (now solve the equation using distributive property) 6+4=x 10=x Tuhduh!! All done using the substitution property.

Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "equals" etc. Also use ^ to indicate powers (eg x-squared = x^2). Neither y2x nor x 2y5 is an equation.

2x-y=3 2/3x-y=-1

Algebraic equations with two variables will need two equations to be able to solve it. Then, you can solve it with either substitution, adding/subtracting them together, or graphing! Those are the basic steps... For example: An instance of substitution: 2x + 1 = y + 2 x + y = 3 You could isolate y in the second equation to equal y = 3-x. Then in the first equation, substitute y with what it equals to 2x + 1 = 3-x+2 Then you can solve for x!

When using substitution the answer to y0.5x plus 2 -y-2x plus 4 is y = -2 (x-1.

Mathematical substitution is the process of using one equation to solve for multiple variables. For example: Equation 1: x + y = 4 Equation 2: 2x + y = 16 Using equation 1, solve for y: y = 4 - x <-- Plug this into equation 2. This is substitution because you are replacing y in equation 2 with what y is equal to in equation 1. 2x + y = 16 ----> 2x + (4 - x) = 16 Now you can solve for x: x + 4 = 16; x = 12 You can then substitute the value of x back into the equation that is solved for y: y = 4 - 12; y = -8 Check both equations: Equation 1: -8 + 12 = 4; 4 = 4 (Correct) Equation 2: 2(12) + (-8) = 16; 24 - 8 = 16; 16 = 16 (Correct) We have successfully used substitution to solve for two different variables, x and y.

If you mean (1) y + 3x = 22 and (2) y + 2x = 16, then (1) y = 22 - 3x (sub this into (2)) (2) (22 - 3x) + 2x = 16 -x = -6 x = 6 y = 22 - 3x = 22 -3(6) = 4 solution: (6,4)

(2,3)

If you mean: y = 2x+2 then the slope is 2 and the y intercept is 2